The Effectiveness of Internet of Things Applications in a Personal Learning Environment in Developing Cognitive Achievement in Programming Skills for the Intermediate School Students in Rabigh Governorate - Altayari, Manahi Saleh; Almohammadi, Najwa Atayan (Journal of Curriculum and Teaching Methodology, 2023)
The research aimed to reveal the effectiveness of Internet of Things applications in a personal learning environment in developing cognitive achievement in programming skills among intermediate school students in Rabigh Governorate, The research used the semi-experimental approach, The research materials and tools were represented in the preparation of a personal learning environment and the cognitive achievement test for programming skills, and the research sample consisted of (60) female students of the first grade intermediate were distributed to two equivalent control groups numbering (30) students, and experimental numbering (30) students, and the results of the research resulted in a statistically significant difference between the average scores of the experimental group and the control group in the post-test of cognitive achievement as a whole and at each level of the test (remembering, understanding, application) in favor of the experimental group. The study recommended the need to benefit from the applications of the Internet of Things in the personal learning environment in the development of educational and cognitive achievement of students in the intermediate school.
Keywords: Internet of Think Applications; Personal Learning Environment; Programming Skills